¿Pesimismo jarnesiano?: glosas comparatistas a El aprendiz de brujo - Armando Pego Puigbó (Revista de Filología Románica, 2010)
In the last twenty years the Benjamín Jarnés’ work has been vindicated by a new generation of critics. Besides some general studies, modern editions of the jarnesian novels and essays have been offered, in order to be placed according to their merits into the literary canon of the twentieth century. From the analysis of the most relevant contributions, this article reconsiders the historical and cultural causes that could explain why the Spanish vanguard novel is not completely acknowledged nowadays, as the poetry of the generation of 27 or even the European modernist narrative is indeed. The recent publication of El aprendiz de brujo, a posthumous novel by Jarnés, is used to show so much the fidelity to an aesthetical creed between modernist and post-modernist as its own limits.